The influence of soybean genotypes and HTC-processing method on trypsin inhibitor activity of soymilk - Stanojević, Slađana P; Barać, Miroljub B; Pešić, Mirjana B; Vucelić-Radović, Biljana V (Journal of Agricultural Sciences (Belgrade), 2016)
Kunitz (KTI) and Bowman-Birk trypsin inhibitor (BBI) are inhibitors of digestive enzymes in raw soybeans. To improve the nutritional quality of soy foods, trypsin inhibitors (TI) are generally inactivated by heat treatment. Soymilk is a turbid and stable colloidal solution, obtained after thermal treatment of soybean. In this study soymilk was made on the pilot-plant scale from six soybean cultivars by the production method that includes hydrothermal cooking (HTC). This procedure is significantly different from the traditional one. The aim of this study was to assess the influence of a HTC-processing for soymilk production and different soybean genotype on trypsin inhibitors content and activity. Obtained soymilk contained BBI in a trace amounts, in the BBI-polymeric forms. BBI- monomeric forms was not detected. The soymilk of the investigated soybean genotypes had very similar KTI levels (2.34-2.99%). Results suggested that soybean genotype does not have substantial effects on the levels of KTI, as well as on the value of residual trypsin inhibitor activity (rTIA). Total content of TI and rTIA was in strong dependence (r=0.91; p